Electrified semitrailer longitudinal wheel-torque control within safe operation and how the communication between vehicle units affects the motion performance - Hermansson, Harald; Tjärnlund Leppämäki, Joakim (My University, 2024)
In the electrification of the heavy duty fleet, electrified semitrailers are a big talking point and a lot of work is being put into researching how they could work and how they should be controlled. This thesis focuses on how two different levels of communication will affect the performance, stability and drive-ability of an electric semitrailer. The first level of communication follows the ISO 11992-2:2014 standard, which mainly allows for only brake-torque requests from the tractor to the trailer (called type 3 communication in this thesis). This will be compared to a new communication interface that allows more request signals from the tractor to the semitrailer and more data in both directions (called type 4 communication). This means all wheel speeds, axle loads and torque requests can be communicated back and forth at all times. Four different controller algorithms were created. One for the type 4 level communication, and three for the type 3 level, where two are equipped with two extra sensors, a coupling force sensor and an articulation angle sensor. The last one only relies on the sensors available in a standard semitrailer according to ISO 11992-2:2014. The controllers were tested in a high-fidelity simulation environment in four different use cases, where their motion performance was measured and compared to a tractor with a non-driven semitrailer. All vehicle combinations performed better than the normal tractor and semitrailer combination, although they were more prone to failures such as jackknifes and rollovers due to the added powertrain on the electrified semitrailers. In conclusion, having an electrified semitrailer can improve the performance of the vehicle, but the level of communication did not have a big impact on the results from the simulated use cases investigated in this thesis.
Keywords: Heavy duty vehicle; Electric semitrailer; Torque distribution; Vehicle dynamics